FORMULASI SEDIAAN KRIM EKSTRAK ETANOL BUNGA KAMBOJA (Plumeria acuminata L.) DAN UJI AKTIVITAS ANTI ACNE - Yuniarti, Rafita; Dalimunthe, Gabena Indrayani; Lubis, Minda Sari; Arianti, Sellin Arina (Jurnal Farmanesia, 2021)
Cambodian flower (Plumeria acuminata L.) contains antioxidant and antibacterial properties, namely flavonoids, tannins, saponins, alkaloids, steroids and glycosides. Kanboja flower ethanol extract (EEBK) was formulated into cream preparations because it tends to be more desirable and more efficient in its use. The research objectives were to formulate frangipani flower ethanol extract as cream soap and to test its activity against acne-causing bacteria. The research methods included: phytochemical screening, simplicia characterization of frangipani flowers, maceration of ethanol extract of frangipani flowers with 96% ethanol solvent, test activity of extracts against acne-causing bacteria by agar diffusion, formulation of cream preparations, test activity of preparations against acne-causing bacteria by diffusion agar. , and evaluation of preparations included: organoleptic test, homogeneity test, pH test, physical stability test, emulsion type test, viscosity test, and irritation test on volunteers. Based on the research results, phytochemical screening of EEBK and frangipani flower simplicia powder has active compounds such as: alkaloids, flavonoids, saponins, tannins, steroids and glycosides. The results of the simplicia characterization of frangipani flowers have a water content of 7.99%, a water-soluble extract content of 26.22%, and an ethanol-soluble extract content of 10.57%. The cream evaluation results in the pH test ranged from 6.0 to 6.1, the viscosity test was between 208-226 mPas, and the physical stability test for 35 days did not change in color, smell, and shape. while the test results of antibacterial activity of the cream on the bacteria Propionibacterium acnes formula I with a concentration of 5% did not produce an inhibition zone, formula II with a concentration of 10% produced an inhibition zone of 8.95 mm -+ 3.79 and formula III with a concentration of 15% produced an inhibition zone of 15, 35 mm -+ 2.59. The conclusion of all the evaluation test results above meet the requirements according to the Indonesian National Standard (1994)